The requirement for calcification differs between ecologically important coccolithophore species. Issue 1 (19th June 2018) - Walker, Charlotte E.; Taylor, Alison R.; Langer, Gerald; Durak, Grażyna M.; Heath, Sarah; Probert, Ian; Tyrrell, Toby; Brownlee, Colin; Wheeler, Glen L.
Summary: Coccolithophores are globally distributed unicellular marine algae that are characterized by their covering of calcite coccoliths. Calcification by coccolithophores contributes significantly to global biogeochemical cycles. However, the physiological requirement for calcification remains poorly understood as non‐calcifying strains of some commonly used model species, such as Emiliania huxleyi, grow normally in laboratory culture. To determine whether the requirement for calcification differs between coccolithophore species, we utilized multiple independent methodologies to disrupt calcification in two important species of coccolithophore: E. huxleyi and Coccolithus braarudii . We investigated their physiological response and used time‐lapse imaging to visualize the processes of calcification and cell division in individual cells. Disruption of calcification resulted in major growth defects in C. braarudii, but not in E. huxleyi . We found no evidence that calcification supports photosynthesis in C. braarudii, but showed that an inability to maintain an intact coccosphere results in cell cycle arrest. We found that C. braarudii is very different from E. huxleyi as it exhibits an obligate requirement for calcification. The identification of a growth defect in C. braarudii resulting from disruption of the coccosphere may be important in considering their response to future changes in ocean carbonate chemistry. Abstract : See also the Commentary on this article byGal, 220 : 5–7 .